PENGGUNAAN ZEOLITE SINTETIS DALAM PENGERINGAN GABAH DENGAN PROSES FLUIDISASI INDIRECT CONTACT - Affian Widjanarko; R. Ridwan; M. Djaeni; R. Ratnawati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2012)
Drying grain commonly used in Indonesia is drying by using sunlight. Drying is still constrained by the type of season. The research objective to accelerate the use of zeolite grain drying process, determine the relationship inlet air temperature dryer drying rate, and determine the relationship of the inlet air flow rate of air at the rate of drying. The operating conditions in this experiment is the drying air temperature ((30oC; 40oC; 50oC and 60oC), drying air flow rate (1 m / s; 1.5 m / s, 2 m / s and 2.5 m / s) and zeolite 1 kg. The research was carried out by flowing dry air at specific operating conditions and then brought into contact with the grain in the fluidized bed to obtain the water content of 12-14%. The results obtained indicate the temperature of 30oC, Nc = 0.0082, while the temperature of 60oC, Nc = 0.0138. In the air flow rate of 1 m / s, Nc = 0.0094 while the air flow rate of 2.5 m / s, Nc = 0.0118. From this data it can be concluded that the higher the temperature and the rate of air dryer, the drying rate wil be faster.